(untitled) (REMUNOM, 2026)
Digital marketing is a set of strategies and practices used to promote products, services, or brands through digital platforms. It encompasses a variety of online channels, including social media, search engines, email, websites, and mobile apps. Therefore, the objective of this article is to understand how a supermarket in Campos Belos, Goiás, uses digital marketing through social media to influence consumers to purchase its products and services. The research types used were descriptive, exploratory, bibliographic, and case study. The method employed was qualitative. The data collection instrument was a semi-structured questionnaire with nine questions, administered to the company’s marketing coordinator and general manager. The survey was conducted on June 14, 2025, at the company’s premises. The study found that the use of social media platforms like Instagram and WhatsApp as relationship-building tools helps the company and directly impacts consumers’ decisions when purchasing products and services, confirming the importance of digital media for customer acquisition, retention, and loyalty. Therefore, these social networks, when applied as direct communication tools between companies and customers, offer opportunities for engagement, feedback, and the building of lasting bonds.